Psychiatry and its discontents - Scull, Andrew, 1947- (University of California Press, 2019)
"Psychiatry and Its Discontents provides a wide-ranging and critical perspective on the psychiatric enterprise. The book's historical sweep is broad, ranging from the age of the asylum to the rise of psychopharmacology and the dubious triumphs of "community care." Freud and Foucault, Christian Science and Scientology, psychosurgery and modern drug treatments, trauma and the effects of war on the human psyche, the siren song of neuroscience, and the predicaments confronting the profession at the dawn of the new millennium are but some of the issues considered here. Collectively, the essays that make up Psychiatry and Its Discontents provide a vivid and compelling portrait of the recurring crises of legitimacy that mad-doctors (as they were once called) have endured, and of the impact of psychiatry's ideas and interventions on the lives of those afflicted with mental illness"--Provided by publisher